Luis Felipe Noé : pintura y conflicto civil argentino (1820-1830) a través de la Serie federal - Néstor Ponce (Amnis)
This article analyzes the aesthetics of the Argentine painter Luis Felipe Noé and his works’ relationship with a critical reading of history. My piece includes the 1961 Serie Federal paintings whose theme refers to the "anarchy of the 1820s" in Argentina. During this period, the country lived a period of great political and military instability, following opposition from the capital Buenos Aires and the provinces. To address this chaotic period of history, which shares similarities with that of the late 50s and early 60s and with the confrontation between Peronists and anti-Peronists, the painter proposed to "assume" chaos, ie Sarmiento overcome opposition and "Civilization or Barbarism" recognized the values of "barbarism" as a manifestation of otherness identity. Noé’s aesthetics is one of transgression: he questions the pictorial language and proposes a "barbaric beauty" which questions the traditional message of the painting Argentina gender his work proposes a rereading of history which goes against the grain of the official history.